2017
DOI: 10.1249/mss.0000000000001068
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Profile of a Multiple Tour de France Winning Cyclist

Abstract: The aerobic physiology and PPO values indentified are among the highest reported for professional road cyclists. Notably, the participant displayed both a high V˙O2peak and GE, which is uncommon among elite cyclists and may be a contributing factor to their success in elite cycling. In addition, performance in HH conditions was strong, suggesting effective thermoregulatory physiology. In summary, this is the first study to report physiological characteristics of a multiple Tour de France champion in close to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 42 publications
0
37
0
1
Order By: Relevance
“…Then, the power that each rower achieved at the anaerobic threshold (WAT), at 4 mmol (W4) and 8 mmol (W8) was extrapolated. For the WAT calculation, the D-max method was used [44,45].…”
Section: Determination Of Thresholdsmentioning
confidence: 99%
“…Then, the power that each rower achieved at the anaerobic threshold (WAT), at 4 mmol (W4) and 8 mmol (W8) was extrapolated. For the WAT calculation, the D-max method was used [44,45].…”
Section: Determination Of Thresholdsmentioning
confidence: 99%
“…Based on a recent report of performance testing in a world-class cyclist (Bell, Furber, Someren, Anton-Solanas, & Swart, 2017), a 15 min rest period was provided between submaximal and maximal (VO 2 max) treadmill exercise testing. The VO 2 max test was administered in 2-min stages at 0% grade, beginning at 80 m/min and working up to the velocity at lactate threshold (295 m/min).…”
Section: Submaximal and Maximal Oxygen Consumption (Vo 2 Max) Exercmentioning
confidence: 99%
“…Case studies reported training organization of ultra-endurance athletes in running, triathlon, cross-country skiing and cycling [1][2][3][4]. In these case studies, the athletes put in more than 1 500 h yearly, with an average of 14 ± 2 sessions per week [1,3,4]. Very high yearly training volumes have been observed for cyclists: 24 000 km [5], runners: 10 000 km [6], and swimmers: 3 500 km [7], corresponding to 28 ± 3 h per week.…”
Section: Introductionmentioning
confidence: 99%